2019
DOI: 10.1186/s12931-019-1058-2
|View full text |Cite
|
Sign up to set email alerts
|

Human lung fibroblast-to-myofibroblast transformation is not driven by an LDH5-dependent metabolic shift towards aerobic glycolysis

Abstract: Background Idiopathic pulmonary fibrosis (IPF) is a fatal respiratory disease characterized by aberrant fibroblast activation and progressive fibrotic remodelling of the lungs. Though the exact pathophysiological mechanisms of IPF remain unknown, TGF-β1 is thought to act as a main driver of the disease by mediating fibroblast-to-myofibroblast transformation (FMT). Recent reports have indicated that a metabolic shift towards aerobic glycolysis takes place during FMT and that metabolic shifts can di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 40 publications
4
25
0
Order By: Relevance
“…It facilitates pro-inflammatory responses and tissue remodeling in airways [ 15 ]. TGF- β was also identified as the main cytokine that induces augmented matrix deposition mainly through fibroblast recruitment and transformation in the IPF lung [ 16 ]. TGF-β can also stimulate and increase reactive oxygen species (ROS) production that leads oxidant and antioxidant imbalance which in turn can activate latent TGF-β developing a profibrogenic cycle [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…It facilitates pro-inflammatory responses and tissue remodeling in airways [ 15 ]. TGF- β was also identified as the main cytokine that induces augmented matrix deposition mainly through fibroblast recruitment and transformation in the IPF lung [ 16 ]. TGF-β can also stimulate and increase reactive oxygen species (ROS) production that leads oxidant and antioxidant imbalance which in turn can activate latent TGF-β developing a profibrogenic cycle [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…A range of pathophysiological conditions including cancer and fibrotic lung diseases are thought to involve a reprograming of cellular metabolism, with skewing toward aerobic glycolysis, suggesting a potential therapeutic target. We showed that the addition of a potent LDH5 inhibitor resulted in a dose dependent reduction in extracellular acidification rate, consistent with a reduction in the production of lactate from pyruvate ( 22 ). Our system therefore allowed the evaluation of a novel compound in fully differentiated human cells, with the observed metabolic effects predicted from its designed mode of action.…”
Section: Discussionmentioning
confidence: 58%
“…This method also has transferability across other disease models where cells are grown on transwell inserts, in particular where there is also a close association between altered glucose metabolism and disease risk ( 5 , 15 , 17 ). In principle this technique would open up additional avenues for metabolic research beyond epithelial monocultures, such as cocultures with fibroblasts which also undergo significant metabolic shifts in disease-relevant conditions ( 22 ). This would support development of novel therapeutic strategies for targeting epithelia-fibroblast crosstalk in idiopathic pulmonary fibrosis and related fibrotic interstitial lung diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Image analysis was performed as previously described 53,54 . Briefly, using the building blocks of Perkin Elmer´s Columbus Image Analysis system, first nuclei acquired with the Hoechst channel were detected using the building block (BB) “nuclei.” Second, cells were defined with the BB “find cytoplasm” from the FITC channel.…”
Section: Methodsmentioning
confidence: 99%